The role of radiation therapy in management parotid cancer therapy - Santini, Alejandro; Torres, Miguel; Apardian, Robert (Cirugía del Uruguay, 1999)
he authors briefly analyse the clinical features of carcinomas of the parotid, clinical history, presentation and paraclinical tests necessary for staging. Different treatments are analysed in depth with emphasis on radiation therapy. lndications for radiation therapy: 1. Non surgical tumors 2. Non resectable tumors 3. Operated tumors with risk factors (high degree tumors, advanced tumors) 4. Recidives T he more frequent techniques for radiation therapy are detailed. Last, the authors develop a personal series of patients with cancer of the parotid who were referred to the oncological centers where they work as radiation therapy oncologists.